Life and works of Augustin Augier de Favas (1758–1825), author of "Arbre botanique" (1801). Issue 1 (April 2017) - Hellström, N. P.; André, G.; Philippe, M.
Abstract : Augustin Augier's "Arbre botanique" ("botanical tree") (1801), a diagram representing the natural order of plants in the shape of a family tree, is today a standard reference in histories of systematics and phylogenetic trees. The previously unidentified author was a nobleman from Saint-Tropez, a schoolteacher and a priest in the Société de l'Oratoire de Jésus et de Marie immaculée. His biography and two previously unnoticed publications, as well as his correspondence with the Institut national in Paris, are discussed. Knowledge of Augier's identity, his life and works sheds new light upon his taxonomic theories, and helps us to understand his "Arbre botanique". Long before the tree was made into an icon of evolutionism, Augier used it to demonstrate the beauty and perfect order of divine creation. Abstract : En 1801, Augustin Augier publiait son "Arbre botanique", diagramme représentant l'ordre naturel des plantes sous la forme d'un arbre généalogique, considéré aujourd'hui comme une référence de base par les historiens de la systématique et des arbres phylogénétiques. L'auteur, resté jusqu'ici inconnu, était un gentilhomme originaire de Saint-Tropez, enseignant et prêtre de la Société de l'Oratoire de Jésus et de Marie immaculée. Nous présentons sa première biographie ainsi que deux ouvrages inédits de lui et sa correspondance avec l'Institut national à Paris. La connaissance de l'identité d'Augier, de sa vie et de ses travaux, jette une nouvelle lumière sur ses théories taxonomiques et nous aide à comprendre son "Arbre botanique". Longtemps avant que l'arbre ne devienne une icône de l'évolutionnisme, Augier l'utilisa pour démontrer la beauté et l'ordre parfait de la création divine.